Counteracting Ingrained Practices of Community Development in the US South The Case of Klondike/Smokey City in Memphis TN, USA - Raciti, Antonio (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2018)
In the US, the field of community development has recently become a contested terrain where non-governmental entities intertwine their initiatives with the ones proposed and implemented by public authorities. This paper explores the assumptions and some of the problematic and unresolved issues tied to the rhetoric of community development exploring the case of the historic African American neighborhood of Klondike Smokey City (KSC). In particular, the paper shares some of the lessons learned during an action-oriented research process carried out by a newly born partnership between the KSC Community Development Corporation (CDC) and the City and Regional Planning (CRP) Department at the University of Memphis. The paper reflects on how approaches to planning research inspired by action-research might be conducive in revealing some of the most challenging issues faced by self-organization practices and how these might be addressed through collaborative planning processes.